2015
DOI: 10.4103/1687-8426.165905
|View full text |Cite
|
Sign up to set email alerts
|

Automatic tube compensation versus pressure support ventilation as a weaning mode: does it make a difference?

Abstract: Background Automatic tube compensation (ATC) is one of the newer weaning modes that seem promising to improve the weaning process.Objective To evaluate the benefit of ATC in hastening and improving the weaning process. Patients and methodsIn a prospective randomizedcontrolled trial, all eligible patients of Assiut Chest Department who were mechanically ventilated were included during the period from April 2010 to March 2012. They were divided into two groups, 88 patients weaned by pressure support ventilation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Of the 19 studies further assessed for eligibility, 9 were excluded (Figure 1). In addition to 31 previously included trials, we identified 10 new full publications, including 1 full publication that replaced a previously included abstract publication. Of the 40 trials included (n = 6797 randomized and n = 6716 patients with outcomes), 9 were new trials (n = 3130 patients analyzed), 6 trials compared 3 SBT techniques (but for 1 of the 3-arm trials, the 5-cm H 2 O and 10-cm H 2 O CPAP groups were combined for a single comparison with the third T-piece group), and 1 trial compared 4 SBT techniques (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 19 studies further assessed for eligibility, 9 were excluded (Figure 1). In addition to 31 previously included trials, we identified 10 new full publications, including 1 full publication that replaced a previously included abstract publication. Of the 40 trials included (n = 6797 randomized and n = 6716 patients with outcomes), 9 were new trials (n = 3130 patients analyzed), 6 trials compared 3 SBT techniques (but for 1 of the 3-arm trials, the 5-cm H 2 O and 10-cm H 2 O CPAP groups were combined for a single comparison with the third T-piece group), and 1 trial compared 4 SBT techniques (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Only 2 trials (5.0%) assessed outcomes in a blinded manner. Twenty-one trials (52.5%) were judged to have complete outcomes reporting, including 6 new trials . Finally, 27 trials (67.5%) conducted an intention-to-treat analysis, and 33 trials (82.5%) did not stop early for benefit.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations